The Ruble between the hammer and the anvil: Oil prices and economic sanctions - Christian Dreger; Jarko Fidrmuc; Konstantin Kholodilin; Dirk Ulbricht (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
The exchange rate fluctuations strongly affect the Russian economy, given its heavy dependence on foreign trade and investment. Since January 2014, the Ruble lost 50% of its value against the US Dollar. The fall of the currency started with the conflict between Russia and Ukraine. The impact of the conflict on Russia may have been amplified by sanctions imposed by Western countries. However, as Russia is heavily dependent on exports of natural resources, the oil price decline starting in Summer 2014 could be another factor behind the deterioration. By using high frequency data on nominal exchange and interest rates, oil prices, actual and unanticipated sanctions, we provide evidence on the driving forces of the Ruble exchange rate. The analysis is based on cointegrated VAR models, where fundamental long-run relationships are implicitly embedded. The results indicate that the bulk of the depreciation can be related to the decline of oil prices. In addition, unanticipated sanctions matter for the conditional volatility of the variables involved.
Keywords: C22; F31; F51; 330; military conflict; sanctions; oil prices; Ruble depreciation